Handbook of poverty in India : perspectives, policies, and programmes - Radhakrishna, R. (ed.); Ray, Shovan (ed.) (New Delhi, 2005)
The poverty situation is markedly different from what prevailed three decades back. Poverty is not only an economic phenomenon but also a social phenomenon. From the 1990s, with the analyses of the causes underlying poverty and the discussions on the efficacy of alternative remedial measures receiving greater attention from policymakers such as raising livelihood opportunities through the endowment of land and non-land assets, by generating employment opportunities, and through public intervention for large-scale food-for-work programme the position changed. The present book represents a culmination of these intellectual efforts and policy concerns in the country that evolved over this period. Thus, the volume provides an account of the incidence, trends, and determinants of poverty in India and reviews the situation in the context of deprivations, empowerment, role of poor in governance, its geographical concentration, major policies and programme implementation, and the legislativ e and other initiatives taken by the government.
Keywords: Poverty-India-Handbook